Curcumin in a model skin lotion formulation - Suhaimi, Hamdan; Ahmad, Faujan B.H.; Friberg, Stig E. (Elsevier, 1995)
A lamellar liquid crystalline region was identified in a typical skin lotion formulation system composed of a mixture of isostearic acid and triethanolamine (TEA) at 65:35 (w/w), decane, and water (the temperature was controlled at 30 °C). The interlayer spacings were determined by a small‐angle X‐ray diffraction technique. Incorporation of a natural dye, curcumin, resulted in lower interlayer spacings and higher penetration of water into the layered structure. However, the higher penetration of water was not apparent at all compositions of isostearic acid:TEA, decane, and water.